As atividades de aventura e os profissionais que atuam nesse campo, sob a ótica dos professores das instituições de ensino superior e dos gestores das empresas do setor em Belo Horizonte - Marlon Teodoro Silva (2020)
The present study arises with the intention of understanding what teachers from higher education institutions and managers say about approaches and distances between training processes and professional performance within the scope of Adventure Activities in Belo Horizonte. For this, we move towards investigating perceptions and understandings about what would be a professional profile valued by managers as well as what has been done by teachers in order to influence the insertion of Physical Education professionals in this market. The work was directed through the qualitative approach. Bibliographic research, research diary, semi-structured interview and content analysis were the tools used to answer the questions in this study. We conclude that, in the case of teachers from higher education institutions, previous experiences with adventure activities and the understanding that these activities are possibilities of performance are, above all, determining factors to influence the insertion of Physical Education professionals in this market. Using Adventure Activities as a subterfuge to bring up discussions on behalf of the environment was a reality observed in all the speeches of teachers and, for this reason, the objectives of sustainable development were highlighted in this study. When it comes to the opinion of managers who work in the adventure activities market, the valued professional profile is summarized in skills that meet, to a certain extent, demands of the labor market, such as: technical mastery of the area, proactivity and public service.